Tenfold reduction of Brownian noise in high-reflectivity optical coatings - Cole, Garrett D.; Zhang, Wei; Martin, Michael J.; Ye, Jun; Aspelmeyer, Markus (Nature photonics, 2013)
Thermally induced fluctuations impose a fundamental limit on precision measurement. In optical interferometry, the current bounds of stability and sensitivity are dictated by the excess mechanical damping of the high-reflectivity coatings that comprise the cavity end mirrors. Over the last decade, the dissipation of these amorphous multilayer reflectors has at best been reduced by a factor of two. Here, we demonstrate a new paradigm in optical coating technology based on direct-bonded monocrystalline multilayers, which exhibit both intrinsically low mechanical loss and high optical quality. Employing these ‘crystalline coatings’ as end mirrors in a Fabry–Pérot cavity, we obtain a finesse of 150,000. More importantly, at room temperature, we observe a thermally limited noise floor consistent with a tenfold reduction in mechanical damping when compared with the best dielectric multilayers. These results pave the way for the next generation of ultra-sensitive interferometers, as well as for new levels of laser stability. By employing monocrystalline semiconductor materials as high-quality optical coatings, the long-standing challenge of minimizing the optical phase noise produced by Brownian motion in a multilayer has been overcome. A thermally limited noise floor consistent with a tenfold reduction in mechanical damping relative to that in the best dielectric multilayers is achieved.